Edible Leafy Plants from Mexico as Sources of Antioxidant Compounds, and Their Nutritional, Nutraceutical and Antimicrobial Potential: A Review - Mateos-Maces, Lourdes (Antioxidants (Basel), 2020)
A review of indigenous Mexican plants with edible stems and leaves and their nutritional and nutraceutical potential was conducted, complemented by the authors’ experiences. In Mexico, more than 250 species with edible stems, leaves, vines and flowers, known as “quelites,” are collected or are cultivated and consumed. The assessment of the quelite composition depends on the chemical characteristics of the compounds being evaluated; the protein quality is a direct function of the amino acid content, which is evaluated by high-performance liquid chromatography (HPLC), and the contribution of minerals is evaluated by atomic absorption spectrometry, inductively coupled plasma-optical emission spectrometry (ICP-OES) or ICP mass spectrometry. The total contents of phenols, flavonoids, carotenoids, saponins and other general compounds have been analyzed using UV-vis spectrophotometry and by HPLC. For the determination of specific compounds such as phenolic compounds, flavonoids, organic acids and other profiles, it is recommended to use HPLC-DAD, UHPLC-DAD, UFLC-PDA or gas chromatography-mass spectrometry. The current biochemical analysis and biological evaluations were performed to understand the mechanisms of action that lead to decreased glucose levels and lipid peroxidation, increased hypoglycemic and antitumor activity, immune system improvement, increased antibacterial and antifungal activity and, in some cases, anti-Helicobacter pylori activity.